2019
DOI: 10.1530/joe-18-0412
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Lh cells caused by cell proliferation and recruitment of existing cells

Abstract: Luteinizing hormone (Lh) and follicle-stimulating hormone (Fsh) control reproduction in vertebrates. Using a transgenic line of medaka, in which green fluorescent protein expression is controlled by the endogenouslhbpromotor, we studied development and plasticity of Lh cells, comparing juveniles and adults of both genders. Confocal imaging and 3D reconstruction revealed hypertrophy and hyperplasia of Lh cells in both genders from juvenile to adult stages. We show that Lh cell hyperplasia may be caused by recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 77 publications
5
42
1
Order By: Relevance
“…Contrary to what has been previously described for Lh cells (Hildahl et al 2012), we did not observe any Fsh cell outside of the pituitary in medaka. We then observed that similar to in Lh cells (Fontaine et al 2019), the number of Fsh cells as well as the percentage of cells they represent in the pituitary increase between juvenile and adult stages. In addition, we demonstrate that the cell volume is also increasing between juvenile and adult stages, which is in agreement with the previous observation where Lh cell size was also observed to increase.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Contrary to what has been previously described for Lh cells (Hildahl et al 2012), we did not observe any Fsh cell outside of the pituitary in medaka. We then observed that similar to in Lh cells (Fontaine et al 2019), the number of Fsh cells as well as the percentage of cells they represent in the pituitary increase between juvenile and adult stages. In addition, we demonstrate that the cell volume is also increasing between juvenile and adult stages, which is in agreement with the previous observation where Lh cell size was also observed to increase.…”
Section: Discussionmentioning
confidence: 54%
“…Counting of Fsh cells was performed blindly using Cell Profiler software (v2.1.0 (Carpenter et al 2006)) as described in Fontaine et al (2019), from eight to nine animals from each sex and stage. Double-labeled cells (BrdU/hrGfpII or BrdU/DsRed2) after steroid and BrdU treatments were manually counted using Fiji software and cell-counter plugin.…”
Section: Counting and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fsh cells were located in the median part of the proximalis pars distalis (PPD). Homozygous tg( fshb :DsRed2) fish were crossed with the previously established tg( lhb :hrGfpII) line (Figure 1E-H) established by Hildahl et al (36) and recently validated by Fontaine et al (47), to obtain the double tg( lhb :hrGfpII/ fshb :DsRed2). In the double tg line, the two cell types expressing either fshb or lhb were clearly separated (Figure 1I-L).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we inferred that the dsred2 -positive cells produce Fsh hormone and can therefore be referred to as Fsh cells. We then crossed tg( fshb :DsRed2) fish with fish from the previously established tg( lhb :hrGfpII) line (36, 47) (Figure 1E-H) and examined the spatial distribution of Fsh and Lh cells. In agreement with prior studies in teleosts (7), in the double tg( lhb :hrGfpII/ fshb :DsRed2) medaka Fsh and Lh were expressed by distinct pituitary cells, thereby validating its use to simultaneously study Fsh and Lh cells (Figure 1I-L).…”
Section: Discussionmentioning
confidence: 99%